Identification and characterization of microRNAs in ovary and testis of Nile tilapia (Oreochromis niloticus) by using solexa sequencing technology. - Jun Xiao (Public Library of Science (PLoS), 2014)
MicroRNAs (miRNAs) are endogenous non-coding small RNAs which play important roles in the regulation of gene expression by cleaving or inhibiting the translation of target gene transcripts. Thereinto, some specific miRNAs show regulatory activities in gonad development via translational control. In order to further understand the role of miRNA-mediated posttranscriptional regulation in Nile tilapia (Oreochromis niloticus) ovary and testis, two small RNA libraries of Nile tilapia were sequenced by Solexa small RNA deep sequencing methods. A total of 9,731,431 and 8,880,497 raw reads, representing 5,407,800 and 4,396,281 unique sequences were obtained from the sexually mature ovaries and testes, respectively. After comparing the small RNA sequences with the Rfam database, 1,432,210 reads in ovaries and 984,146 reads in testes were matched to the genome sequence of Nile tilapia. Bioinformatic analysis identified 764 mature miRNA, 209 miRNA-5p and 202 miRNA-3p were found in the two libraries, of which 525 known miRNAs are both expressed in the ovary and testis of Nile tilapia. Comparison of expression profiles of the testis, miR-727, miR-129 and miR-29 families were highly expressed in tilapia ovary. Additionally, miR-132, miR-212, miR-33a and miR-135b families, showed significant higher expression in testis compared with that in ovary. Furthermore, the expression patterns of the miRNAs were analyzed in different developmental stages of gonad. The result showed different expression patterns were observed during development of testis and ovary. In addition, the identification and characterization of differentially expressed miRNAs in the ovaries and testis of Nile tilapia provides important information on the role of miRNA in the regulation of the ovarian and testicular development and function. This data will be helpful to facilitate studies on the regulation of miRNAs during teleosts reproduction.